Qualitative Study of Costus speciosus Koen ex Retz Sm and its potentiality against Human Pathogenic Microbes - Gomathinayagam, Muthiah (International Journal of Pharmaceutical & Biological Archive, 2014)
Qualitative Study of Costus speciosus Koen ex Retz Sm and its potentiality against Human Pathogenic Microbes